Costurero de la memoria: kilómetros de vida y de memoria: memorias disímiles, sueños compartidos (2020)
This monograph collects the research process that I carried out thanks to the company of the members of the memory seamstress: kilometers of life and memory. The thesis seeks to show how the textile can become an activator of dialogue and an excuse to build collective memory and generate processes of symbolic repair. Through five interviews, participant observation and the review of documents associated with the subject, I can to understand that knitting goes beyond a simple manual practice. In this document I show the process, its relationship with the theory learned in the course of the master's degree and my own life. This story comes from my heart, I did it with great sincerity and passion, because we are the story that runs through us and to learn how people build memory, I also made memory. I learned to heal and to forgive and I understood that in these complex and simple acts at the same time we can find peace.